Effect of a coronary-heart-disease-associated variant of ADAMTS7 on endothelial cell angiogenesis. (March 2020) - Pu, Xiangyuan; Chan, Kenneth; Yang, Wei; Xiao, Qingzhong; Zhang, Li; Moore, Andrew D.; Liu, Chuanju; Webb, Tom R.; Caulfield, Mark J.; Samani, Nilesh J.; Zhu, Jianhua; Ye, Shu
Abstract: Background and aims: Recent studies have unveiled an association between ADAMTS7 gene variation and coronary artery disease (CAD) caused by atherosclerosis. We investigated if the ADAMTS7 Serine214-to-Proline substitution arising from a CAD-associated variant affected angiogenesis, since neovascularization plays an important role in atherosclerosis. Methods and results: ADAMTS7 knockdown in vascular endothelial cells (ECs) attenuated their angiogenesis potential, whereas augmented ADAMTS7-Ser214 expression had the opposite effect, leading to increased ECs migratory and tube formation ability. Proteomics analysis showed an increase in thrombospondin-1, a reported angiogenesis inhibitor, in culture media conditioned by ECs with ADAMTS7 knockdown and a decrease of thrombospondin-1 in media conditioned by ECs with ADAMTS7-Ser214 overexpression. Cleavage assay indicated that ADAMTS7 possessed thrombospondin-1 degrading activity, which was reduced by the Ser214-to-Pro substitution. The pro-angiogenic effect of ADAMTS7-Ser214 diminished in the presence of a thrombospondin-1 blocking antibody. Conclusions: The ADAMTS7 Ser217-to-Pro substitution as a result of ADAMTS7 polymorphism affects thrombospondin-1 degradation, thereby promoting atherogenesis through increased EC migration and tube formation. Graphical abstract: Image 1 Highlights: Serine-to-proline substitution in ADAMTS7 in endothelial cells inhibits angiogenesis. ADAMTS7 degrades thrombospondin-1, a potent angiogenesis inhibitor. Augmented expression of ADAMTS7-Ser214 increases endothelial cell migration and neo-vessel tube formation. The pro-angiogenic effect of ADAMTS7-Ser214 diminishes in the presence of a thrombospondin-1 blocking antibody.